Perancangan Ulang Website Gesha Menggunakan Pendekatan Lean UX dan Metode System Usability Scale - Istikomah, Ayu; Panduardi, Farizqi; Hidayat, Alfin (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
The coffee industry in Indonesia is growing with the emergence of various new coffee shop brands. Social media such as Instagram and Facebook are often used as digital marketing tools, but are only effective for attracting visual attention and through active communities. On the other hand, creating a website is considered more effective because it allows for detailed information delivery and deeper performance analysis. Gesha Coffee Roastery is one of the businesses that uses a website as a digital marketing strategy to reach customers and increase brand awareness. However, in this case, the Gesha website experienced several problems, namely the absence of features that can display contactable contacts, there were still empty website pages, and several buttons that were still not functioning. This study was directed at testing and redesigning the Gesha website. The design was carried out by applying the Lean UX approach method, while the assessment of task performance was carried out through a post-task study test by applying the SEQ method and the SUS method for usability evaluation was carried out with a post-study test. The final result of the redesign of the Gesha website with the application of the Lean UX method is a prototype that has a final SUS score of 82 on grade B with the result